The National Strategy to Transforming the Reality of Financial Inclusion in Algeria: An Analytical Study in Light of Indicators - Kenza Thabet (Journal of Excellence for Economics and Management Research, 2026)
This study aims to highlight the current state of financial inclusion in Algeria by analyzing indicators that measure the extent to which its dimensions have been realized. It sheds light on Algeria's position within the ESCWA Financial Inclusion Index 2023 relative to select countries in the Arab region. Furthermore, the study identifies the national strategy adopted to enhance financial inclusion in the country. Utilizing both descriptive and analytical methodologies. The study concludes that the level of financial inclusion in Algeria is considerably low across both access and usage indicators of financial services. According to ESCWA Financial Inclusion Index 2023, Algeria achieved low levels across all dimensions of financial inclusion, as well as a low overall financial inclusion index score compared to other Arab countries. Additionally, while the "Digital Algeria 2030" national vision and the National Strategy for Financial Transformation 2025–2030 represent significant steps toward changing the reality of financial inclusion in Algeria, they are considered to have been adopted at a very late stage.